2014
DOI: 10.1177/1721727x1401200213
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin in Inflammatory Skin Conditions

Abstract: The conserved serine/threonine kinase mammalian target of rapamycin (mTOR) is a major regulator of survival growth, proliferation and motility, in response to mitogens, energy and nutrient levels. Dysregulation of mTOR pathway has been observed in various inflammatory or neoplastic human diseases. To assess the potential involvement of mTOR in some of the most common inflammatory skin diseases, and its interaction with other inflammatory mediators, we investigated mTOR expression in psoriasis, allergic contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In the skin, reports show increased levels of both mTORC1 and mTORC2 activity during progression from normal keratinocytes to pre-cancerous actinic keratosis, and finally to NMSC [63]. Dysregulation of the mTOR pathway in keratinocytes is not limited to NMSC but has also been observed in multiple inflammatory skin diseases, including acne, psoriasis and dermatitis [64, 65]. In addition, it has been shown that mTORC1 inhibition with topical rapamycin blocks dermal inflammation that is associated with the hyperproliferative response to tumor promotion [66].…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, reports show increased levels of both mTORC1 and mTORC2 activity during progression from normal keratinocytes to pre-cancerous actinic keratosis, and finally to NMSC [63]. Dysregulation of the mTOR pathway in keratinocytes is not limited to NMSC but has also been observed in multiple inflammatory skin diseases, including acne, psoriasis and dermatitis [64, 65]. In addition, it has been shown that mTORC1 inhibition with topical rapamycin blocks dermal inflammation that is associated with the hyperproliferative response to tumor promotion [66].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of adaptive immunity, leptin is involved in T cell generation, maturation and survival [93]. It mediates Th1 phenotype differentiation by increasing IFN-γ, TNF-α and IL-2 production, while it inhibits rapamycin-induced Treg cells, by increasing activation of mammalian target of rapamycin (mTOR), which is up-regulated in psoriatic skin as well as in others inflammatory skin conditions (allergic contact dermatitis and atopic dermatitis) [90,94]. Moreover, leptin promotes CD4+ cell differentiation into Th17 cells and augments IL-17A production [95].…”
Section: Leptinmentioning
confidence: 99%
“…[3] When active, mTORC1 phosphorylates and activates its downstreameffectorribosomalproteinS6kinase1(S6K1)involved incellproliferation. [1] Someinflammatoryskindiseasesarecharac-terizedbyelevatedlevelsofmTOR, [4][5][6] andtherearefewreports indicating an increase of mTOR and S6K1 in psoriasis too. [4,7] Up tonow,thelinkbetweenmTORC1andTNFα in psoriasis has not beenyetelucidatedeventhoughitiswellknownthatTNFα is an upstream signal of mTORC1 and also one of main protagonists of the disease.…”
Section: Introductionmentioning
confidence: 99%